Proposals for the analysis and comparison of types, traditions and ceramic styles of northern Chile based on their visible and concealed aspects - Erazo Gutiérrez, Fernanda (Revista Chilena de Antropología, 2023)
It proposed a model of pottery analysis which seeks to reconstruct traditions and styles by comparing visible and concealed aspects of pottery types. This assumes that each vessel has a set of visible features that highlight by the naked eye (forms, surface treatments, decorations); and a group of less visible or concealed aspects that are inferred (pastes, manufacturing techniques, firing). The visible aspects can be indicators of certain regional or local borders, while the concealed aspects can represent communities of potters that share a specific technical identity. This perspective is majorly based on approaches of the chaîne opératoire and technological style and could contribute to the study of the interaction among groups from different localities. It is proposed would be suitable for northern Chile archaeology, considering the good preservation of the material and the previous development of typological sequences in its different areas.